2012
DOI: 10.1016/j.bbmt.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Differentiation from Hematopoietic Stem Cells: A Comparative Analysis of Heparin- and Stromal Cell–Supported Methods

Abstract: Natural killer (NK) cells differentiated from hematopietic stem cells (HSCs)may have significant clinical benefits over those from adult donors, including the ability to choose allo-reactive donors and potentially more robust in vivo expansion. Stromal-based methods have been used to study NK differentiation from HSCs. Stroma and cytokines support NK differentiation, but may have considerable regulatory hurdles. Recently, a clinical grade heparin-based method has been reported and could serve as an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…It could be that additional signals are required in our system for KIR expression. In the same study the authors found higher CD16 expression on NK cells generated using a heparin-based system compared to those generated using the EL08.1D2 feeder layer [14]. The generation of CD56 + CD16 + cells from either PBSC (100% CD16 + ) [43] or CBSC (24% CD16 + ) has been reported [44].…”
Section: Discussionmentioning
confidence: 83%
“…It could be that additional signals are required in our system for KIR expression. In the same study the authors found higher CD16 expression on NK cells generated using a heparin-based system compared to those generated using the EL08.1D2 feeder layer [14]. The generation of CD56 + CD16 + cells from either PBSC (100% CD16 + ) [43] or CBSC (24% CD16 + ) has been reported [44].…”
Section: Discussionmentioning
confidence: 83%
“…In particular, expansion and differentiation of HPCs allows the generation of clinically applicable NK cell products with high purity and functionality. 25 Nevertheless, we and others have observed that NK cells generated under stroma-free culture conditions using IL-15 and IL-2 have low surface expression of CD16 and only a subset (5-10%) express KIRs, 23,37 raising questions about NK cell potency and alloreactivity following adoptive transfer. Moreover, clinical studies reported so far show that adoptively transferred allogeneic NK cells have a relatively short lifespan in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dezell et al have shown that NK cell expansion from hematopoietic progenitors using stromal cells appears to increase the yield of NK cells compared with stromal-free conditions, perhaps by differentiating less committed progenitors into the NK cell lineage. 62 Despite this potential advantage, stromal-based expansions are logistically more challenging to use under GMP conditions, potentially limiting their application in the clinical setting.…”
Section: Nk Cells Expanded Using Irradiated Ebv-lcl Feeder Cellsmentioning
confidence: 99%